Proceedings of the 10th EAI International Conference on Pervasive Computing Technologies for Healthcare 2016
DOI: 10.4108/eai.16-5-2016.2263335
|View full text |Cite
|
Sign up to set email alerts
|

Design Challenges in Converting a Paper Checklist to Digital Format for Dynamic Medical Settings

Abstract: We describe a mobile digital checklist that we designed and developed for trauma resuscitation-a dynamic, fast-paced medical process of treating severely injured patients. The checklist design was informed by our analysis of user interactions with a paper checklist that was introduced to improve team performance during resuscitations. The design process followed an iterative approach and involved several medical experts. We discuss design challenges in converting a paper checklist to its digital counterpart, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The QI team originally planned to convert the tool from paper to electronic format, but end users have consistently advocated for the continued use of the “index card” format due to its ease of use and portability. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The QI team originally planned to convert the tool from paper to electronic format, but end users have consistently advocated for the continued use of the “index card” format due to its ease of use and portability. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Checklists and other cognitive aids have also caught up with this digitization trend in healthcare [1,7,21,29,33,35]. Checklists are different from EHRs because they support compliance with standardized protocols rather than just documentation.…”
Section: Related Workmentioning
confidence: 99%
“…Checklists are different from EHRs because they support compliance with standardized protocols rather than just documentation. Prior studies have shown that replacing paper forms with electronic checklist systems in medical contexts has had positive effects on task performance and teamwork [1,7,21,29,33,35,37]. Agarwala et al [1], for example, found that an electronic checklist for anesthesia handoffs improved relay and retention of critical patient information.…”
Section: Related Workmentioning
confidence: 99%
“…Certain hurdles may make them reluctant to adopt a digital system, such as prior investment and familiarity with a current system (known as baby duck syndrome ) [ 4 ] and availability, training, and the position of the system [ 3 ]. Although it is feasible to use digital forms in medicine, it has its design constraints, including limited display size and the challenge of replicating the user experience of paper forms or checklists [ 5 ]. These constraints can be handled; however, there are many conflicting guidelines available on appropriate user-centric designs.…”
Section: Introductionmentioning
confidence: 99%